Unraveling the Mechanisms of Zn Efficiency in Crop Plants: From Lab to Field Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Many agricultural crops worldwide suffer from zinc (Zn) deficiency. Despite widespread interest in Zn, plant professionals often lack current information on this indispensable essential mineral nutrient. G. Hacisalihoglu, PhD, in Unraveling the Mechanisms of Zinc Efficiency in Crop Plants, and a host of recognized experts address this gap with the up-to-date importance of Zn nutrition. This book examines research aimed at understanding how plants uptake and utilize Zn. It has been peer-reviewed and multi-authored by expert plant biology scientists with related expertise. The editor provides a comprehensive overview of zinc (Zn) nutrition in plants, seeds, roots, and soil, which renders this book a good reference for plant biology professionals. Agricultural sustainability in the time of the growing world population will be one of the major challenges in the next 30 plus years. Zn is one of the most important essential mineral nutrients required for metabolic processes, so a shortage of Zn constrains crop yield and quality worldwide. Zinc efficiency and higher growth and yield under low Zn supply make it a promising sustainable solution for developing cultivars that are zinc efficient. Several articles are included in this book that provide an overview of current developments and trends in the times of high-throughput genomics and phenomics data analysis. Furthermore, this book presents research findings in various experimental models and areas ranging from maize to alfalfa, flax, and sorghum.Unraveling the Mechanisms of Zinc Efficiency in Crop Plants is a must read for researchers and plant biology professionals.